Pengaruh Budaya Organisasi Terhadap Kinerja Pegawai Pada Biro Perencanaan Sekretariat Jenderal Kementerian Lingkungan Hidup dan Kehutanan Republik Indonesia - A, Andri; Purbaningrum, Dini Gandini; Handayani, Nida (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study highlights two main issues in the office of the planning bureau of the Ministry of Environment and Forestry. First, the work instructions given by superiors to subordinates are not optimal. Second, the time discipline of the employees still needs to be improved, with some employees leaving and entering the office at times that do not adhere to the designated schedule. The aim of this study is to identify the influence of organizational culture on employee performance in the Planning Bureau of the Ministry of Environment and Forestry of the Republic of Indonesia. The organizational culture theory used in this study is from Victor Tan, which consists of individual initiative, risk tolerance, supervision, communication patterns, and management support. Meanwhile, the employee performance theory used is taken from Bernardin Russell, which includes job quantity, job quality, timeliness, cost efficiency, supervision, and interpersonal influence. The research method used is associative research with a quantitative approach. The sample used is a non-probability sampling technique with a saturated sample type, where the entire population of employees in the Planning Bureau of the Ministry of Environment and Forestry, which amounts to 67 respondents, is taken as the sample. The analysis technique used is simple linear regression using SPSS version 25. The results of the study show that organizational culture has a positive and significant influence on employee performance, with a significant value of 0.000 0.05. The organizational culture variable obtains a significant value of 1.119, which means that if the organizational culture value increases by one point, employee performance will increase by 1.119. Based on the R square test, the R Square value is 0.634 or 63.4%. This indicates that the organizational culture variable affects employee performance by 63.4%. The rest is influenced by other variables that are not discussed in this study.